Values, environmental concern and economic concern as predictors of enterprise environmental responsiveness - Potocan, Vojko; Nedelko, Zlatko; Peleckienė, Valentina; Peleckis, Kęstutis (Journal of Business Economics and Management, 2016)
This article reports on examination of the relationships between manager’s personal values, their attitudes toward concern for environment, concern for economic results and enterprise environmental responsiveness. Schwartz’s list of values and statements about the environmental and economic concerns is used. We analyzed 1179 managers’ answers from Slovenian enterprises with structural equation modeling. Manager’s concern results: (a) for environment positively and significantly and (b) for economics negatively and insignificantly, in influence on enterprise environmental responsiveness. Two value dimensions significantly influence enterprise environmental responsiveness and one negatively. Environmental concern mediates the effect of three, and concern for economic results mediates the effect of two value dimensions on enterprise’s environmental responsiveness. Generalization can be limited due to the focus on one Central Europe country; future examination is needed. Findings are useful for the development of enterprises’ pro-environmental behavior and development of enterprise value system. A model of enterprise’s environmental responsiveness is developed.